To Finish in German and Mainland Scandinavian: Telicity and Incrementality. (14th March 2019) - Spalek, Alexandra Anna; Sæbø, Kjell Johan
Abstract: Among the words that describe initial or final parts of events, words describing finishing stand out in a number of ways: in a language like English, there is a transitive verb which is singularly flexible regarding the type of event retrievable from the context; in a language like German, there is no verb but there is a verbal particle; in either case, there is a requirement of telicity and there is a requirement of theme incrementality. The present paper documents these facts and offers an analysis of the verbal particle.